Cellular Cholesterol Distribution Influences Proteolytic Release of the LRP-1 Ectodomain - Dekky, Bassil; Wahart, Amandine; Sartelet, Hervé; Féré, Michaël; Angiboust, Jean-François; Dedieu, Stéphane; Piot, Olivier; Devy, Jérôme; Emonard, Hervé (Frontiers in Pharmacology, 2016)
Low-Density Lipoprotein Receptor-related Protein-1 (LRP-1) is a multifunctional matricellular receptor composed of a large ligand-binding subunit (515-kDa α-chain) associated with a short trans-membrane subunit (85-kDa β-chain). LRP-1, which exhibits both endocytosis and cell signaling properties, plays a key role in tumor invasion by regulating the activity of proteinases such as matrix metalloproteinases (MMPs). LRP-1 is shed at the cell surface by proteinases such as membrane-type 1 MMP (MT1-MMP) and a disintegrin and metalloproteinase-12 (ADAM-12). Here we show by using biophysical, biochemical and cellular imaging approaches that efficient extraction of cell cholesterol and increased LRP-1 shedding occur in MDA-MB-231 breast cancer cells but not in MDA-MB-435 cells. Our data show that cholesterol is differently distributed in both cell lines; predominantly intracellularly for MDA-MB-231 cells and at the plasma membrane for MDA-MB-435 cells. This study highlights the relationship between the rate and cellular distribution of cholesterol and its impact on LRP-1 shedding modulation. Altogether, our data strongly suggest that the increase of LRP-1 shedding upon cholesterol depletion induces a higher accessibility of the sheddase substrate, ie LRP-1, at the cell surface rather than an increase of expression of the enzyme.